Communicating papal authority in the Middle Ages - Ozawa, Minoru, 1973- (New York : Routledge, 2023)
"This book bridges Japanese and European scholarly approaches to ecclesiastical history to provide new insights into how the papacy conceptualised its authority and attempted to realise and communicate that authority in ecclesiastical and secular spheres across Christendom. Adopting a broad, yet cohesive, temporal and geographical approach that spans the Early to the Late Middle Ages, from Europe to Asia, the book focuses on the different media used to represent authority, the structures through which authority was channelled and the restrictions that popes faced in so doing, and the less certain expression of papal authority on the edges of Christendom. Through twelve chapters that encompass key topics such as anti-popes, artistic representations, preaching, heresy, the crusades, and mission and the East, this interdisciplinary volume brings new perspectives to bear on the medieval papacy. The book demonstrates that the communication of papal authority was a two-way process effected by the popes and their supporters, but also by their enemies who helped to shape concepts of ecclesiastical power. Communicating Papal Authority in the Middle Ages will appeal to researchers and students alike interested in the relationships between the papacy and medieval society and the ways in which the papacy negotiated and expressed its authority in Europe and beyond"--
Introduction / Minoru Ozawa, Thomas W. Smith, and Georg Strack -- Part I. Representations of Papal Authority: 1. Authority at a Distance: Popes, their Media, and their Presence Felt in the Frankish Kingdom / Shigeto Kikuchi -- 2. Imitatio Christi in Papal Synodal Sermons, 1095-1274 / Georg Strack -- 3. John XXII as a Wavering Preacher: The Pope's Sermons and the Norms of Preaching in the Beatific Vision Controversy / Yuichi Akae -- 4. Franciscan Identity and Iconography in the Assisi Tapestry commissioned by Pope Sixtus IV / Alessandro Simbeni -- Part II. Structural Restrictions and Challenges to Papal Authority: 5. Crisis and Antagonism: Contending Popes as a Challenge to Papal Authority / Harald Müller -- 6. Papal Communication and the Fifth Crusade, 1217-1221 / Thomas W. Smith -- 7. 'Having one little wolf at the papal court is not enough': The Limits of Papal Authority in Milanese Affairs in the Mid-Fifteenth Century / Jessika Nowak -- Part III. Papal Authority on the Edges of Christendom: 8. Why did a Viking King meet a Pope? Cnut's Imperial Politics, Scandinavian Commercial Networks, and the Journey to Rome in 1027 / Minoru Ozawa -- 9. Papal Contact with the Mongols: Means of Communication in the Thirteenth Century / Mamoru Fujisaki -- 10. Dei et ecclesiae inimicus: A Correspondence between Pope Gregory IX and John III Batatzes / Koji Murata -- 11. Medieval Heretics in the East: A Heresiological Label for Bosnian Bogomils/Patarenes in the Thirteenth Century / Hisatsugu Kusabu -- 12. The Papacy and Crusading in the Far North? A Forgotten Religious Frontier of Medieval Latin Christendom / Takahiro Narikawa -- Index.
Keywords: Catholic Church -- Doctrines -- History -- To 1500.; Popes -- Primacy -- History of doctrines -- Middle Ages, 600-1500.; Popes -- Temporal power -- History -- Middle Ages, 600-1500.; Church and state -- History; Pastoral theology -- Catholic Church -- History -- To 1500.; HISTORY / Medieval